Place of imidazoline receptor agonists in the treatment of arterial hypertension - D. V. Nebieridze; A. S. Safaryan; E. I. Ivanova; E. A. Poddubskaya (Столичная издательская компания, 2023)
The review is devoted to one of the most controversial issues of modern antihypertensive therapy - the role of new generation sympatholytics - selective I1-imidazoline receptor agonists (AIRs). In modern European recommendations, AIR (moxonidine rilmenidine), along with other centrally acting drugs (reserpine, alpha-methyldopa, clonidine), are mainly intended for additional therapy in rare cases of resistant hypertension, when other treatment options have been ineffective. Nevertheless, AIR invariably finds its place in Russian recommendations for the treatment of arterial hypertension (AH). This class of drugs is recommended for patients with AH in combination with metabolic syndrome and obesity. It is noted that an important property of AIR is its positive effect on carbohydrate and lipid metabolism. This information is based on an analysis of Russian and foreign studies, which convincingly indicate that this class of drugs not only provides adequate and long-term blood pressure control, but also has the above-mentioned positive metabolic effects. At the same time, AIRs are much less likely to cause side effects characteristic of older generation centrally acting drugs. Thus, AIRs have become firmly established in clinical practice in Russia for the treatment of patients with AH in certain clinical situations.